GLP-1-Exendin-4/IgG4 (Fc) Fusion Protein as a Novel Drug for Diabetes Treatment - Gan, Y.; Dang, N.; Qu, Z.; Shi, R.; Ding, L.; Wang, L.; Pang, S. (Experimental and Clinical Endocrinology & Diabetes, 2015)
In this paper, we aimed to look for a potent long acting GLP-1 receptor agonist for diabetes treatment. In this work, we constructed the eukaryotic expression vector of GLP-1-Exendin-4/IgG4 (Fc)-pOptiVEC™-TOPO® and then transfected it into Chinese hamster ovary DG44 (CHO/DG44) cells using liposome method. Then the beta-cell line INS-1 cells were treated with purified GLP-1-Exendin-4/IgG4 (Fc) fusion protein (0.01, 0.1, 1.0 mM respectively) and randomly assigned to 2 groups, each group were then grown in KRB buffer in the presence of 2.8 mM or 16.8 mM glucose for 2 h separately. In addition, single dose of fusion protein was intraperitoneally injected into male CD1 mice for pharmacokinetic study. Besides, multiple low doses of streptozotozin (STZ) induced diabetes mice were used to evaluate the effect of fusion protein for anti-diabetes in male CD1 mice. GLP-1-Exendin-4/IgG4 (Fc) had stimulatory effect on insulin secretion glucose-dependently from INS-1 cells in a dose-dependent manner. Pharmacokinetic studies showed that the GLP-1 level increased significantly after injecting fusion protein and maintained a higher level for 200 h. Besides, multiple-low-dose STZ-induced diabetes mice which received intraperitoneal injections of fusion protein did not show sign of diabetes. Our results indicated that GLP-1-Exendin-4/IgG4 (Fc) fusion protein retained native GLP-1 activities and had effect on long-term glucose regulation. All the results suggest that this fusion protein may serve as a potent long acting GLP-1 receptor agonist.
Keywords: glucagon-like peptide-1; exendin-4; GLP-1-Exendin-4/IgG4 (Fc) fusion protein; pharmacokinetic study; streptozotocin (STZ)-induced diabetes mice